2013
DOI: 10.1038/srep03052
|View full text |Cite
|
Sign up to set email alerts
|

On the Predictability of Future Impact in Science

Abstract: Correctly assessing a scientist's past research impact and potential for future impact is key in recruitment decisions and other evaluation processes. While a candidate's future impact is the main concern for these decisions, most measures only quantify the impact of previous work. Recently, it has been argued that linear regression models are capable of predicting a scientist's future impact. By applying that future impact model to 762 careers drawn from three disciplines: physics, biology, and mathematics, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 26 publications
1
91
1
2
Order By: Relevance
“…This is considerably a more complex problem. For example, a recent attempt to predict the future evolution of the h-index of authors, based on linear regression models applied to their past performance [81], turned out to be largely unsuccessful [82], highlighting that cumulative impact measures (such as the h-index) are not suitable bases for prediction approaches.…”
Section: Impact Predictionmentioning
confidence: 99%
“…This is considerably a more complex problem. For example, a recent attempt to predict the future evolution of the h-index of authors, based on linear regression models applied to their past performance [81], turned out to be largely unsuccessful [82], highlighting that cumulative impact measures (such as the h-index) are not suitable bases for prediction approaches.…”
Section: Impact Predictionmentioning
confidence: 99%
“…For example, it has been reported that the future h-index 6 of an investigator is moderately predictable on the basis of the current h-index, number of articles, publications in prestigious journals, and diversity of the journals in which the articles are published 7 ; however, the h-index would not be appropriate to inform funding decisions because this metric has several flaws, including its intrinsic autocorrelation and the fact that its predictive power is heavily dependent on career age and is least accurate for young researchers. 8 The annual number of citations at the time of prediction has been claimed to be the best predictor of future citations. 9 The number of publications and citations in the previous 5 years has been found to correlate with the citation impact of a grant.…”
Section: Can Productivity Be Measured?mentioning
confidence: 99%
“…Note that I will disregard individual characteristics that change over time, such as the researcher's age or position (Cainelli et al, 2012(Cainelli et al, , 2015Morichika & Shibayama, 2015), and individual characteristics that are fixed in time, such as gender or race (Abatemarco & Dell'Anno, 2013;Hopkins et al, 2013;Sotudeh & Khoshian, 2014). In this paper, my interest is in indices for, rather than determinants of, scientific activity (Penner et al, 2013). Moreover, I will omit papers that use indices to compare countries (e.g., Sangwal, 2013), institutions (e.g., Abramo et al, 2013c), or journals (e.g., Ko & Park, 2013;Tsai, 2014).…”
Section: Introductionmentioning
confidence: 99%